2010
DOI: 10.1007/s10799-010-0075-0
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of hyped technologies: a qualitative study

Abstract: The introduction of new consumer technology is often greeted with declarations that the way people conduct their lives will be changed instantly. In some cases, this might create hype surrounding a specific technology. This article investigates the adoption of hyped technology, a special case that is absent in the adoption literature. The study employs a consumer research perspective, specifically the theory of consumption values (TCV), to understand the underlying motives for adopting the technology. In its o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 77 publications
(114 reference statements)
0
41
0
1
Order By: Relevance
“…Researchers also found that behavioral intention was comprised of three determinants: attitude, subjective norm, and perceived behavioral control (Ajzen, 1991;Holden& Karsh, 2010). The TAM includes the TRA's indirect influence of attitudes however it uses two more specific constructs: perceived usefulness and perceived ease-of-use (Davis, 1989;Hedman & Gimpel, 2010).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Researchers also found that behavioral intention was comprised of three determinants: attitude, subjective norm, and perceived behavioral control (Ajzen, 1991;Holden& Karsh, 2010). The TAM includes the TRA's indirect influence of attitudes however it uses two more specific constructs: perceived usefulness and perceived ease-of-use (Davis, 1989;Hedman & Gimpel, 2010).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…The theory was originally presented in 1991, and since then it has been used to explain consumer choice in fields as diverse as higher education (Lai, To, Lung, & Lai, 2012), teenagers' smoking behavior (Albaum, Baker, Hozier, & Rogers, 2002), technology adoption (Hedman & Gimpel, 2010;Turel, Serenko, & Bontis, 2010) and ethical consumption (Green & Peloza, 2011). TCV has shown substantial explanatory as well as prescriptive power in more than 200 studies concerning the choice of buying versus not buying, the choice of product type, and the choice of brand type (Sheth et al, 1991a).…”
Section: The Theory Of Consumption Values Perspectivementioning
confidence: 99%
“…A thorough understanding of true fad-like behaviour calls for more detailed analysis across both competing products (e.g., other vendors' smart phones) and similar technologies (e.g., the iTouch TM and iPad TM ) alongside their own competitors. The impact of technology hype that precedes product releases by leading vendors such as Apple or Google also complicates the model presented (Hedman and Gimpel, 2010).…”
Section: Future Research Directionsmentioning
confidence: 99%